Preliminary Study of Micronucleus Frequencies and Responses in Thyroid Cancer Patients After Treatment with 131I Therapy - Basri, I. K. H.; Lusiyanti, Y.; Ramadhani, D.; Tetriana, D.; Dewi, A. R.; Purnami, S.; Suvivan, V. A.; Gani, M. R. A.; Kisnanto, T. (Atom Indonesia, 2024)
Radioiodine has become the most widely used to treat an overactive thyroid (hyperthyroidism) and thyroid cancer worldwide. The present research aimed to study the association between micronuclei (MN) frequencies, and follow-up responses after treating thyroid cancer patients with iodium-131(131I). The detection of the MNs assay was carried out by Giemsa staining from lymphocytes obtained from twenty-four thyroid cancer patients one week after receiving 131I treatment at Dharmais Cancer Center Hospital, Jakarta, Indonesia. Follow-up for clinical and laboratory responses grouped into good (stable) and bad (progressive, refractory, and dropout patients) responses, was observed one and six months after treatment. All patients received radioiodine with an activity dose of 30 - 200 μCi. The mean MN frequency in the good response group was 14.22, and that of bad response patients was 17.22. There was no statistically significant difference in MN frequency (p>0.05) between the two groups of patients after six months of treatment.